SCHOOL TEACHERS UNDERGO TRAINING AT USM FOR NEW COMPUTER SCIENCE CURRICULUM - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PENANG, 2 May 2017 – The Universiti Sains Malaysia (USM) School of Computer Sciences has been appointed as instructors by MDEC (Malaysia Digital Economy Corporation) to provide training to school teachers in preparing them for the new computer science subject curriculum.